PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI PADA KANTOR DINAS PENDAPATAN PROVINSI JAWA TIMUR (Studi Kasus Di Kabupaten Nganjuk) - Andayani, Sari; Astri Sari, dan Tatar Rany (Journal of Accounting and Strategic Finance, 2009)
Quality have come to the vital topic to all researcher of caused by its is change in this matter service competition go together the global change and change of life style society, service quality frequently in viewing as a[n strategy for organization to reach the difference’s service, assess the customer, and customer/ client satisfaction. Pursuant to background hence this research target is to know the influence of Service Quality to Consumer Satisfaction at On Duty Earnings of Province of East Java. This research population is officer which follows the share and playing important role in decision making at On Duty Earnings of Province of East Java Nganjuk amounting to 24 respondents. While to analyze the influence Reliability, Responsiveness, Assurance and Empathy to Consumer Satisfaction of at On Duty Earnings of Province of East Java Nganjuk, statistic test used by is technique analyses the doubled linear regression. Pursuant to hypothesis test got by that Reliability and Empathy have an effect on to consumer satisfaction, Responsiveness and Assurance do not have an effect on to Consumer Satisfaction of at On Duty Earnings of Province of East Java Nganjuk.   Keywords: Reliability, Responsiveness, Assurance, Empathy and Consumer Satisfaction